1991
DOI: 10.1113/jphysiol.1991.sp018830
|View full text |Cite
|
Sign up to set email alerts
|

Motor units of the fourth deep lumbrical muscle of the adult rat: isometric contractions and fibre type compositions.

Abstract: SUMMARY1. Isometric twitch and tetanic tensions were recorded from whole muscles and single motor units in fourth deep lumbrical muscles isolated from young adult (60 days) rats. Muscles were superfused with oxygenated Ringer solution at 25°C except where stated otherwise.2. It was confirmed that the muscle is supplied most commonly by eleven motor axons, nine via the lateral plantar nerve (LPN), and two via the sural nerve (SN). Motor units whose axons were isolated from either LPN or SN were studied. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 27 publications
2
44
0
Order By: Relevance
“…Table 4 Mean (SD) and range (in square brackets) of ratios of the properties characterising the twitch and the fused tetanus. The results of comparisons of dierences between mean values for the three types of motor units are presented at the bottom part of the Table. (T Tw á (T Tet ) )1 Ratio of tensions of the twitch to the tetanus, v Tw á (m Tet ) )1 ratio of velocities of increase in tension of the twitch to the tetanic contraction measured from the baseline to 50% of the peak value for both kinds of contraction, Ampl MMG Tw á (Ampl MMG Tet ) )1 ratio of amplitudes of MMG signals during the twitch to the tetanus) It is well known that the value of the T Tw :T Tet ratio is the highest for FF and the lowest for the S type of motor unit (Bagust et al 1973;Stephens and Stuart 1975;Gates et al 1991;Celichowski and Grottel 1993). In addition, it was observed that ratios of MMG amplitudes and velocities if changes in tension are also the highest for FF and the lowest for S motor units.…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 Mean (SD) and range (in square brackets) of ratios of the properties characterising the twitch and the fused tetanus. The results of comparisons of dierences between mean values for the three types of motor units are presented at the bottom part of the Table. (T Tw á (T Tet ) )1 Ratio of tensions of the twitch to the tetanus, v Tw á (m Tet ) )1 ratio of velocities of increase in tension of the twitch to the tetanic contraction measured from the baseline to 50% of the peak value for both kinds of contraction, Ampl MMG Tw á (Ampl MMG Tet ) )1 ratio of amplitudes of MMG signals during the twitch to the tetanus) It is well known that the value of the T Tw :T Tet ratio is the highest for FF and the lowest for the S type of motor unit (Bagust et al 1973;Stephens and Stuart 1975;Gates et al 1991;Celichowski and Grottel 1993). In addition, it was observed that ratios of MMG amplitudes and velocities if changes in tension are also the highest for FF and the lowest for S motor units.…”
Section: Discussionmentioning
confidence: 99%
“…Adult rat lumbrical muscles have contraction properties similar to those of EDL muscles (20), but their major advantage is that they are thin enough to allow a suitable measurement of tyrosine release (Fig. 2), which is not possible with EDL muscles because of the inevitable necrosis of inner muscle fibers (3).…”
Section: Discussionmentioning
confidence: 99%
“…Innervated muscle spindles viewed after microdissec-tion from unoperated mouse DL muscles contained be-tween two and five intrafusal muscle fibres, each less than 10 1-m in diameter, as described in other mouse muscles (Tourtellotte et al, 2001;Desaki et al, 2010) or rat lum-brical muscles (Porayko and Smith, 1968;Ovalle, 1972;Gates et al, 1991;Kucera et al, 1991). Each spindle was supplied by one large primary afferent axon, penetrating the capsule and terminating in annulospiral endings that wrapped the equatorial region of the intrafusal muscle fibres (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…We therefore tested for functional com-petence of the annulospiral endings themselves, using FM1-43 as a fluorescent reporter. Muscle stretch, which depolarises annulospiral sensory endings, facilitates up-take of amphipathic styryl dyes such as FM1-43 and RH795 (Gates et al, 1991;Bewick et al, 2005). We dis-sected lumbrical muscles 3-5 days after axotomy and pinned preparations of these at extended lengths in phys-iological saline containing 8-1-M FM1-43.…”
Section: Other Possible Determinants Of Slow Sensory Axonal Degenerationmentioning
confidence: 99%